The National Minimum Wage and Hours of Work: Implications for Low Paid Women. - Connolly, S; Gregory, M (2002)
The largest group of beneficiaries from the introduction of the National Minimum Wage in the UK were women working part-time. A potential threat to these wage gains is a reduction in the working hours available, with part-time (flexible) jobs particularly vulnerable. This paper reports a range of difference-in-difference estimates using individual-level data from the New Earnings Survey and the British Household Panel Survey. No significant changes in hours worked by either full- and part-time women are found one, two and three years after the NMW, and no change in the probabilities of remaining in full- or part-time work or transiting between the two.